Microbubbles as a Contrast Agent for Neurosonography and Ultrasound-Guided Catheter Manipulation: In Vitro Studies - Widder, Donald J.; Simeone, Joseph F. (American Journal of Neuroradiology, 1986)
Tissue-equivalent ultrasound phantoms, including models of the ventricular system and cyst phantoms, may be useful for developing expertise in both biopsy procedures and shunt catheter placement that use ultrasound guidance. These phantoms have been constructed (1) to assess the ability to position biopsy needles and manipulate shunt catheters with conventional angiographic guidewires and (2) to evaluate the usefulness of microbubbles as an ultrasound contrast agent. Optimal catheter and needle position and catheter patency are demonstrated with microbubbles generated by hand injection of small volumes of saline, a safe ultrasound contrast agent that, to our knowledge, has not been previously exploited in neurosonography. Microbubbles can define biopsy needle location without direct imaging of the biopsy needle; they can also define the extent of communication or separation of fluid-filled or loculated spaces.